2009
DOI: 10.1002/cphc.200800504
|View full text |Cite
|
Sign up to set email alerts
|

Positively Charged Compact Quantum Dot–DNA Complexes for Detection of Nucleic Acids

Abstract: Novel QD-DNA complexes are prepared by simple electrostatic interaction between pegylated amine-functionalized CdSe/ZnS quantum dots (QDs) and DNA. The cationic nature of the amine functionality on the QD surface allows for formation of an electrostatic complex with negatively charged DNA. The presence of polyethylene glycol (PEG5000) molecules on the QD leads to enhanced stability and decreased nonspecific adsorption of DNA on the QD surface. Unlike assembly of QD-DNA based on hydrogen bonding, the present QD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 19 publications
(20 reference statements)
0
61
0
Order By: Relevance
“…17 Most of the reported approaches required covalent conjugation of DNA to the QD surface (e.g., by EDC/NHS coupling reaction), which often decreases the colloidal stability and/or the emission intensity of QDs. 18,19 This limitation can be overcome by the use of a sensing platform relying on the electrostatic interaction of dye-labeled DNA with the oppositely charged QD surface 20 in a similar fashion as in conducting polymer-based detection assays. 4Ϫ8 In this paper, we propose a simultaneous use of conjugated polymers and semiconductor QDs for DNA hybridization detection, which can potentially combine advantages of both light-harvesting and DNA-binding properties of water-soluble polymers with photostability, lightharvesting ability, and FRET donor property of QDs.…”
mentioning
confidence: 99%
“…17 Most of the reported approaches required covalent conjugation of DNA to the QD surface (e.g., by EDC/NHS coupling reaction), which often decreases the colloidal stability and/or the emission intensity of QDs. 18,19 This limitation can be overcome by the use of a sensing platform relying on the electrostatic interaction of dye-labeled DNA with the oppositely charged QD surface 20 in a similar fashion as in conducting polymer-based detection assays. 4Ϫ8 In this paper, we propose a simultaneous use of conjugated polymers and semiconductor QDs for DNA hybridization detection, which can potentially combine advantages of both light-harvesting and DNA-binding properties of water-soluble polymers with photostability, lightharvesting ability, and FRET donor property of QDs.…”
mentioning
confidence: 99%
“…based biosensors. Several sensor designs based on FRET between QDs and dye-labeled biomolecules have been developed [142][143][144]. Zhou et al reported preparation and specific label-free DNA detection of a compact, functional QD-DNA conjugate [145].…”
Section: Quantum Dotsmentioning
confidence: 99%
“…Most of the reported approaches require covalent conjugation of DNA to the QD surface [e.g., by 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide-N-hydroxysuccinimide (EDC/NHS) coupling reaction], which often decrease the colloidal stability and/or the emission intensity of QDs [145]. This limitation can be overcome by the use of a sensing platform relying on the electrostatic interaction of dyelabeled DNA with the oppositely charged QD surface [144]. Peng et al demonstrated a simple DNA-sensing platform on the basis of the FRET between blue-luminescent thioglycolic acid (TGA)-capped CdTe QDs and dye-labeled ssDNA (Fig.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…It was specifically cleavable when expose to HIV-PR and such a peptide-QD system could render the detection sensitivity of HIV-PR in the range of picomol. Lee et al also designed a positively charged compact QD-DNA complex for detection of nucleic acids [16]. The fluorescence of the QD is quenched up to 90% by complexion with 5 -carboxytetramethylrhodamine-(TAMRA-) modified oligonucleotide through FRET.…”
Section: Introductionmentioning
confidence: 99%